Acehytisine suppresses atrial fibrillation in rats with dilated atria caused by chronic volume overload - Xin Cao; Yoshinobu Nagasawa; Chengshun Zhang; Hanxiao Zhang; Megumi Aimoto; Akira Takahara (Elsevier, 2020)
Atrial dilation is an independent risk factor for the development of atrial fibrillation (AF) and modulates the efficacy of anti-AF drugs, leading to the unsatisfactory control of AF. Pre-clinical studies showed anti-AF effects of acehytisine, a multi-ion channel inhibitor, in atria without structural and/or electrophysiological abnormalities, but information is limited regarding its anti-AF efficacy in dilated atria. We evaluated anti-AF effects of acehytisine at 4 and 10 mg/kg intravenously infused over 10 min using 8-week-old Wistar rats (n = 5; male) with atrial dilation caused by aorto-venocaval shunt (AVS). Echocardiography showed that atria were enlarged by +26.9% after one month of operation in AVS rats compared with sham-operated rats (n = 4; male). Electrophysiological examinations indicated burst pacing-induced AF reached 206 s. Acehytisine at doses of 4 and 10 mg/kg decreased the duration of burst pacing-induced AF with prolongation of Wenckebach cycle length and P wave duration in a dose-dependent manner. Importantly, the drug effectively terminated the persistent AF that was resistant to multiple programmed electrical stimulations in one rat. Therefore, these results provide in vivo evidence that acehytisine may be beneficial for preventing and terminating persistent AF in dilated atria. Keywords: Acehytisine, Aorto-venocaval shunt, Volume overload, Atrial fibrillation, Dilated atria